Pelatihan Pengolahan Produk Ikan Asap Untuk Meningkatkan Kualitas Produk - Andi Agus; Ampauleng Ampauleng; Herman Sjahruddin; Yusuf Radja (Universitas Maritim AMNI Semarang, 2023)
Tanah Toa Village is one of the gods that belongs to the Kajang sub-district, Bulukumba district. So far, Tanah Toa has been recognized as a national cultural heritage, especially in the Kajang Dalam area. The non-coastal location makes agricultural activities the dominant activity among the community. Only a few residents run the business of smoking fish. Pera smoked fish business actors obtain raw materials for skipjack tuna in the Bonto Maritime area which is a coastal area. While the production of smoked fish is sold to markets around the Kajang sub-district and the city of Bulukumba. The quality of smoking that is not maximized causes smoked fish to not last long. Smoked fish produced can only last a maximum of 3 days. This makes it difficult for smoked fish production to be traded outside the province or made into souvenirs for tourists who come from out of town. The durability of the smoked fish produced is not yet good because the smoking process only lasts about 2 hours, so the water content is still there. The use of fish smoking technology is also not owned by business actors, making it difficult for business actors to have difficulty in producing good quality smoked fish.